ChemInform Abstract: Application of a Recyclable Fluorous Oxime in the Convenient Synthesis of 3‐Amino‐1, 2‐benzisoxazoles and 4‐Amino‐1H‐2, 3‐benzoxazines. Issue 27 (13th June 2013) - Ang, Wei Jie; Chu, Chi‐Yuan; Chou, Tzyy‐Chao; Lo, Lee‐Chiang; Lam, Yulin
Abstract The strategy comprises linking the respective benzonitrile (I) or (III) to a fluorous oxime tag to give an aryloxime intermediate which then undergoes cyclization with cleavage of the substrate‐tag to provide title compounds (II) and (IV), respectively.